2023
DOI: 10.1097/ta.0000000000004217
|View full text |Cite
|
Sign up to set email alerts
|

It is not all black and white: The effect of increasing severity of frailty on outcomes of geriatric trauma patients

Qaidar Alizai,
Christina Colosimo,
Hamidreza Hosseinpour
et al.

Abstract: Background Frailty is associated with poor outcomes in trauma patients. However, the spectrum of physiologic deficits, once a patient is identified as frail, is unknown. The aim of this study was to assess the dynamic association between increasing frailty and outcomes among frail geriatric trauma patients. Methods This is a secondary analysis of the American Association of Surgery for Trauma Frailty Multi-institutional Trial. Patients ≥65 years present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(98 reference statements)
1
0
0
Order By: Relevance
“…The prior literature has focused on post-operative complications and mortality, neglecting the long-term functional outcomes of these patients [25][26][27]. This cohort of 37 femoral fracture patients living with severe frailty, which mirrors Jones et al's distribution of frailty [18] and prior reported OGC care teams' target populations, demonstrates that while there is a high rate of 1-year mortality following surgical treatment of femur fractures, at the best point of recovery patients report overall positive outcomes in terms of freedom from pain, ambulatory ability, functional independence, and social interaction [5,11,27,36,37].…”
Section: Discussionsupporting
confidence: 65%
“…The prior literature has focused on post-operative complications and mortality, neglecting the long-term functional outcomes of these patients [25][26][27]. This cohort of 37 femoral fracture patients living with severe frailty, which mirrors Jones et al's distribution of frailty [18] and prior reported OGC care teams' target populations, demonstrates that while there is a high rate of 1-year mortality following surgical treatment of femur fractures, at the best point of recovery patients report overall positive outcomes in terms of freedom from pain, ambulatory ability, functional independence, and social interaction [5,11,27,36,37].…”
Section: Discussionsupporting
confidence: 65%